Signal Soft Sets for Atoms Modeling and Signal Soft Topology - Mahmood, Majd Hamid (Iraqi Journal of Science, 2021)
In this paper we define a signal soft set as a mathematical tool to represent and study atoms, anti-atoms, electrons, anti-electrons, protons, and anti-protons, and generate a signal soft topology, with an example of signal soft topology on H2O.